Dr. Omar Haroon — Deep Plane Facelift — Zürich - Haroon, Omar (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Omar Haroon, practicing in Zürich, Switzerland. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003089; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; switzerland; zürich